Parallel mechanisms of polypyrrole self-discharge in aqueous media. Issue 16 (28th April 2015) - Olsson, H.; Qiu, Z.; Strømme, M.; Sjödin, M.
<x xml:space="preserve">Abstract</x> Self-discharge of oxidized polypyrrole is composed of two parallel self-discharge mechanisms and their relative contributions depend on pH and potential.